The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1115/1.1308029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inlet Conditions on the Thermohydrodynamic State of a Fully Circumferentially Grooved Journal Bearing

Abstract: A thermohydrodynamic (THD) analysis of a fully circumferentially grooved hydrodynamic bearing is presented. The pressure distribution is obtained using the short bearing approximation taking into account the viscosity variation in the radial and circumferential coordinates. The axial temperature variation is also included by an axial averaging technique, which incorporates the supply pressure and film entry temperature in the energy equation. It is found that the determination of the lubricant temperature at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…An analysis of the influence of oil inlet conditions on the THD performance of the fully circumferentially grooved journal bearings was performed by Keogh and Khonsari [20]. A simplified axial averaging technique was used, that enabled the groove pressure and the entry temperature to the lubricant film to be explicitly incorporated into the lubricant energy equation and highlighted that the mixing effect must be always taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the influence of oil inlet conditions on the THD performance of the fully circumferentially grooved journal bearings was performed by Keogh and Khonsari [20]. A simplified axial averaging technique was used, that enabled the groove pressure and the entry temperature to the lubricant film to be explicitly incorporated into the lubricant energy equation and highlighted that the mixing effect must be always taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Heshmat and Pinkus 6 studied the mixing inlet October 2016 Vol 49 No 8 l Measurement and Control 257 temperatures in hydrodynamic bearings as a function of a range of operating conditions for both journal and thrust bearings. Keogh and Khonsari 7 introduced a thermohydrodynamic analysis and found that mixing in the inlet groove might cause a significant influence on film entry temperature. Ma and Taylor described an experimental apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have proved that consistent determination of the film entry temperature plays an important role in realistically predicting the bearing temperature distribution. They have therefore provided various algorithms, depending on the groove and bearing type [1,2,3], in order to model the mixing of incoming supply oil with re-circulating oil in the feed grooves. However, a unified treatment of the groove-mixing energy balance independent of the particular geometry has not yet been devised.…”
Section: Introductionmentioning
confidence: 99%